Have Astronauts Visited Neptune? Student Ideas About How Scientists Study The Solar System (Journal of Astronomy & Earth Sciences Education, 2017)
The nature of students’ ideas about the scientific practices used by astronomers when studying objects in our Solar System is of widespread interest to discipline-based astronomy education researchers. A sample of middle-school, high-school, and college students (N=42) in the U.S. were interviewed about how astronomers were able to learn about properties of the Solar System as a follow-up question after specific questions about the nature of the Solar System and its objects. These students often held naive ideas about the practices of astronomy, and 19% of them proposed that humans or robots have returned samples of the planets to Earth for analysis. While the college students provided more sophisticated responses to the questions than the younger students, we found that even they held naive ideas about human sample return and infrequently appealed to studying objects at a distance using telescopes. We propose that students are not receiving specific instruction that allows them to investigate the tools and practices of astronomy, which leads them to rely on their prior knowledge about science practices in other disciplines (e.g., geoscience) when queried about how scientists study the Solar System. This result implies that instruction around the limits of human and robotic spaceflight is needed to allow students to have a more scientific understanding of the practices of astronomy in studying the Solar System.
Keywords: Astronomy Education; Solar System